Aristotle's modal syllogistic - Malink, Marko, 1980- (Harvard University Press, 2013)
"Aristotle was the founder not only of logic but also of modal logic. In the Prior Analytics he developed a complex system of modal syllogistic which, while influential, has been disputed since antiquity--and is today widely regarded as incoherent. In this meticulously argued new study, Marko Malink presents a major reinterpretation of Aristotle's modal syllogistic. Combining analytic rigor with keen sensitivity to historical context, he makes clear that the modal syllogistic forms a consistent, integreated system of logic, one that is closely related to other areas of Aristotle's philosophy."--Book flap